Structural Characterization, Technofunctional and Rheological Properties of Sesame Proteins Treated by High-Intensity Ultrasound - Gul, Osman; Saricaoglu, Furkan Turker; Atalar, Ilyas; Gul, Latife Betul; Tornuk, Fatih; Simsek, Senay (MDPI, 2023)
Plant-derived proteins, such as those from sesame seeds, have the potential to be used as versatile food ingredients. End-use functionality can be further improved by high-intensity ultrasound treatments. The effects of high-intensity ultrasound on the properties of sesame protein isolates from cold-pressed sesame cake were evaluated. The SDS-PAGE demonstrated no significant changes in the molecular weight of proteins. Ultrasound treatments resulted in decreased particle size with a more uniform distribution, resulting in the exposure of hydrophobicity and free -SH groups and increased zeta potential. Although FTIR spectra of proteins were similar after ultrasonication, a partial increase in the intensity of the amide A band was observed. The ultrasound significantly (p loss modulus (G'')). In addition, the gelation temperature of proteins decreased to about 60-65 degrees C with increasing treatment time. Overall, ultrasound is a useful technique for the modification of sesame protein isolates.
Keywords: sesame protein; high-intensity ultrasound; technofunctional properties; structural properties; rheological properties; FUNCTIONAL-PROPERTIES; EMULSIFYING PROPERTIES; PHYSICAL-PROPERTIES; 7S GLOBULIN; PRETREATMENT; SONICATION; ALBUMIN; Food Science & Technology